RetINal Toxicity And HydroxyChloroquine Therapy (INTACT): protocol for a prospective population-based cohort study. Issue 2 (17th February 2022) - Daftarian, Narsis; Lima, Adriana; Marozoff, Shelby; Ojo, Dami; Levasseur, Steve D; Maberley, David A L; Hoens, Alison; Esdaile, John; Dawes, Martin; Aviña-Zubieta, J Antonio; Adante, Beatrice; Bhui, Ravinder Dennis; et al.
Abstract : Purpose: Hydroxychloroquine (HCQ) is an important medication for patients with systemic lupus erythematosus (SLE), rheumatoid arthritis (RA) and other rheumatic diseases. Although it is well-tolerated and cost-effective, the risk of HCQ retinal toxicity is of increasing concern. The aim of this study is to re-examine the HCQ retinal toxicity incidence rate, risk factors and clinical course after discontinuation. Methods: We designed a prospective population-based cohort study in adult patients with SLE or RA, currently receiving HCQ for five or more years, who are residents of British Columbia (BC), Canada. Based on administrative data, we identified 5508 eligible participants (1346 SLE and 4162 RA). They will participate in annual or biannual retinal screening over 5 years in alignment with the recently revised American Academy of Ophthalmology guidelines. To standardise procedures for retinal screening, imaging, diagnostic criteria, severity staging and data transfer, a consensus meeting was convened in December 2019 with participation of BC retinal specialists and the research team. Agreement was attained on: use of spectral domain-optical coherence tomography as the primary objective screening modality; classification of images into categories of normal, equivocal or abnormal; and transferring the equivocal and abnormal images plus corresponding subjective test results via cloud-based server from each clinic to a reading centre. Confirmation of HCQ retinal toxicity diagnoses and severity staging will be performed by three independent and masked reviewers. The incidence of HCQ retinal toxicity will be calculated, accounting for the competing risk of death. Hazard ratios for each risk factor will be calculated for the risk of HCQ retinopathy, after adjusting for confounders. We will also estimate the risk of HCQ retinal toxicity progression over 5 years. Ethics and dissemination: This study has received approval from the University of British Columbia Clinical Research Ethics Board (H20-00736) and the Vancouver Coastal Health Research Institute.